2015
DOI: 10.5535/arm.2015.39.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Hemiparetic Knee Extensor Strength and Balance Function Are Predictors of Ambulatory Function in Subacute Stroke Patients

Abstract: ObjectiveTo identify the potential predictors of ambulatory function in subacute stroke patients, and to determine the contributing factors according to gait severity.MethodsFifty-three subacute stroke patents were enrolled. Ambulatory function was assessed by gait speed and endurance. Balance function was evaluated by the Berg Balance Scale score (BBS) and the Timed Up and Go test (TUG). The isometric muscular strengths of bilateral knee extensors and flexors were measured using an isokinetic dynamometer. Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Testing at higher speeds was intentionally avoided in some studies as individuals with severe weakness following stroke can have difficulty producing torque at higher speeds on their paretic side [14,57]. Most research reports bilateral isokinetic testing of limb muscles [9][10][11][12][13][14][15][16][17][18]20,22,[24][25][26][27][28][29][30][31][32][33][34][35][36][39][40][41][43][44][45]47,[52][53][54][55][56][57]60,[62][63][64]66,67,[70][71][72]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing at higher speeds was intentionally avoided in some studies as individuals with severe weakness following stroke can have difficulty producing torque at higher speeds on their paretic side [14,57]. Most research reports bilateral isokinetic testing of limb muscles [9][10][11][12][13][14][15][16][17][18]20,22,[24][25][26][27][28][29][30][31][32][33][34][35][36][39][40][41][43][44][45]47,[52][53][54][55][56][57]60,[62][63][64]66,67,[70][71][72]…”
Section: Resultsmentioning
confidence: 99%
“…Validity has been demonstrated most often by differences in known groups and known conditions. Specifically, numerous studies have demonstrated that individuals with stroke are weaker, often significantly (SGNF), than controls in both the paretic [11,17,19,28,38,55,63,64] and nonparetic [11,17,23,28,35,38,55,61,63,71,74,78] limbs, that individuals with stroke are weaker (almost always SGNF) on their paretic side than on their nonparetic side [10,13-16,20,22,23,27,28,30,31,33-36, 38,40,41,43,45,47,54,55,67,68,70,72,75,77], that men tend to be SGNF stronger than women [79], that ambulatory individuals tend to be SGNF stronger than nonambulatory individuals [59], and that community ambulators are SGNF stronger than household ambulators [41]. Validity is also supported by correlations between isokinetically measured strengths of different muscle actions [26,48] and between isokinetic strength measures at different speeds [14,62,81].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous results revealed that hemiparetic knee extensor strength is a predictor of gait endurance and that balance function is also a major determinant of gait speed and endurance in subacute stroke patients. During the stance phase of gait, the knee extensors support knee stability, thereby enabling the non-paretic limb to proceed in a swing phase during long-distance walking 20 . Furthermore, knee extensor weakness in stroke patients is caused by a reduction in recruitable motor units and a diminished capacity for oxidative metabolism 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The BBS and TUG measures an ability to body balance while performing functional tasks like weight shifting, sitting, standing and walking. In addition, 10mWT assesses short distant gait function that depends on knee extensor strength, BBS, and TUG scores because the balance function is a major determinant of gait speed in stroke patients [ 37 ]. Also, BBS, TUG and 10mWT measures are mainly related to balance function including horizontal and vertical movement while the 6MWT measures walking endurance which mainly reflects aerobic capacity rather than balance function [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%